Identification of IL-10 competent B cells in swine. (October 2022) - Milburn, Jemma V.; Hoog, Anna; Villanueva-Hernández, Sonia; Mair, Kerstin H.; Gerner, Wilhelm
Abstract: Progress in the phenotypic characterisation of porcine B cells is ongoing, with recent advances in the identification of B1 cell subsets and plasma cells. However, regulatory B cells, commonly identified by interleukin (IL)-10 production, have not been studied in pigs so far. Here we investigate IL-10 expression in B cell subsets in response to CpG-oligodeoxynucleotides, phorbol 12-myristate 13-acetate and ionomycin stimulation in vitro . Our results reflect similar findings in human and mice. We identify a small subset of IL-10 competent B cells, present within both porcine B1 and B2 cell subsets across blood, spleen, mediastinal lymph nodes and lung tissue, with varied differentiation statuses. The capacity for IL-10 production coincided with CD95 expression, suggesting an activated phenotype of IL-10 competent B cells. These findings support the emerging paradigm that B cell IL-10 production is a function of various B cell subsets influenced by activation history and microenvironmental factors. Highlights: Multiple porcine B cell subsets have the capacity for IL-10 production. B1 cells and IgM +  B2 cells are enriched for IL-10 competent B cells. CD95 expression is associated with IL-10 competency.